2020
DOI: 10.33258/birle.v3i4.1343
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Mathematical Anxiety, Learning Motivation and Self-Confidence to Student’s Mathematical Problem Solving

Abstract: The objectives of this study are to: (1) Analyze whether there is a contribution of mathematics anxiety, learning motivation and self-confidence to the ability to solve mathematical problems simultaneously, (2) Analyze whether there is a contribution of mathematics anxiety, learning motivation and self-confidence to the partial mathematical problem solving ability, (3) To analyze how big the contribution of mathematics anxiety, learning motivation and self-confidence to mathematical problem solving abilities s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Khairiyyah (2021) state that mathematics is an important part of the field of science. According to Irhamna (2020) mathematics is a universal science. Mathematics is also seen as the queen of science.…”
Section: Distance Training (Pjj)mentioning
confidence: 99%
“…Khairiyyah (2021) state that mathematics is an important part of the field of science. According to Irhamna (2020) mathematics is a universal science. Mathematics is also seen as the queen of science.…”
Section: Distance Training (Pjj)mentioning
confidence: 99%
“…Mathematics is a universal science. Mathematics is also seen as the queen of science (Irhamna, 2020). Broadly speaking, it can be concluded that mathematical communication consists of oral and written communication.…”
Section: Mathematical Communication Skillsmentioning
confidence: 99%
“…Mathematics is an important part of the field of science. According to Irhamna (2020). Mathematics is a universal science.…”
Section: Introductionmentioning
confidence: 99%